Neodesenvolvimentismo na Amazônia e a política de trabalho, emprego e renda no estado do Pará: elementos para reflexões - PEREIRA, Maria da Glória (Universidade Federal do Pará, 2013)
The aim of this study is to identify the links between the policy of job, employment and income in Pará State and its current strategies of development for Amazon Region which are based on neo-development ideology. This work also intends to emphasize the analyzes concerned on the policy of job, employment and income in Pará State and the recent growth of labor´s overexploitation in the region, caused especially by the structural dependence imposed on underdeveloped capitalist societies such as countries which surround the Amazon Region. The focus on Pará State due to its notable uniqueness to achieve huge projects brought by transnational companies, mainly the mining and electricity ones, which have been encouraged through governmental policies adopted during both the developmentalist stage and neo-developmentalist fase. The neo-development ideology bases the policies of job, employment and income implementation, encourages as well the finance for training courses targeted to fill the lack of qualified workers for the mentioned projects as the autonomous labor through the Job and Income Supplies Programmes. The methodology was qualitatively using secondary sources. First was held bibliographic research and after used various documentary sources ,which included institutional research data, mainly from Seter . The study allowed me to understand that the links that bind the policy on job, employment and income at strategy neo-developmentalist, comply with objective of ensuring the legality practices of labor´s overexploitation, from de process the restructuring of productive capital and the flexibility of labor relations.